PENGARUH MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) TERHADAP HASIL BELAJAR SISWA PADA MATERI BAHAN KIMIA DALAM KEHIDUPAN SEHARI-HARI - Hayatuz Zakiyah; Nuzula Ulfa (UIN AR-RANIRY, 2017)
Based on the observation in SMPN 1 Sukamakmur shown that students VIII were not enough understand in learning chemical matter in life, obstacles of students in studying chemistry based on difficulty in understanding the terms in the science of chemistry. This research aims to understand the influence of PBL learning model on students activities, Study results of students and students response against the implementation of PBL learning to the chemicals matter in daily life of class VIII in SMPN 1 Sukamakmur Aceh Besar. The research was apparent experiment (a quasi experiment) by using one group pretest and posttest design. Data collection were techniques used observation technique were multiple choice test shaped and survey. Data observation and response analyzed by using technique percentage, while test results were analyzed by t-test. The result of student learning activity percentage were about 94% with good criteria and the lowest value of 78 % but it is still on the criteria good. Study results students increased afterwards applied PBL learning model of t-test was obtained tcount > ttable was 20,42 > 2,08. Students response were very are interesting in PBL model by the results was of the percentage who answered â€œyesâ€ was 92,1% and answers â€œnotâ€ was 7,9%.